Implementation of Item Response Theory (IRT) Rasch Model in Quality Analysis of Final Exam Tests in Mathematics - Rahim, Abdul; Haryanto, Haryanto; Abdul Rahim (Journal of Research and Educational Research Evaluation, 2021)
This study was conducted to analyze the test instrument used to measure the ability of students in the odd semester final exam in mathematics. Sampling using purposive sampling technique. These students consist of 67 people. The questions given are in the form of multiple choice questions totaling 40 items related to the odd semester final exam material. The data analysis technique used quantitative descriptive analysis. The Rasch model is used to obtain fit items. This analysis was carried out with the help of Winsteps 3.73 software. From the output of the Winsteps program, 35 items were obtained according to the Rasch model with an average value of Outfit MNSQ for persons and items of 1.09 and 1.09, respectively. While the Outfit ZSTD values for person and item are -0,1 and -0,2 respectively. Meanwhile, the instrument reliability expressed in Cronbach's alpha is 0.77.